PENGARUH PENGGUNAAN VARIASI BERAT ROLLER TERHADAP KONSUMSI BAHAN BAKAR SEPEDA MOTOR MATIC 110 CC - Luthfi Reza Eri Kurniawan; Ranto Ranto; Ngatou Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
In the current era, automatic motorbikes are the most popular motorbikes and are most widely used for everyday purposes. The motorcycle population always increases by around 5 million units every year. Of this amount, around 70% are motorbikes of the matic type, aka scooters. One trick that is usually used by automatic motorbike lovers to upgrade the characteristics of their automatic motorbike is to replace a part called the CVT roller. The aims of this study were: (1) To find out the effect on fuel consumption produced by a 110cc automatic motorcycle using variations in roller weight. (2) Knowing the effect on fuel consumption produced by 110cc automatic motorbikes using variations of engine speed. (3) Knowing the effect of using roller weight variations at RPM variations on fuel consumption on 110cc automatic motorcycles. The research method used is experimental. The research data was obtained by measuring the Honda BeAT New 2018 motorcycle sample. The independent variable is roller weight Variation and Variation of engine rotation. The dependent variable is fuel consumption. The data obtained were then analyzed using quantitative descriptive techniques by describing them in the form of graphs and tables. The results of this study are: (1) The use of variations roller weight 10, 12, and 14 grams have an effect on fuel consumption. The use of a roller that is heavier or lighter than standard (12 grams) has the effect of producing a more different fuel consumption. (2) Variations in engine speed (3500, 5000 and 6500 RPM) have an influence on fuel consumption. Each increase in engine speed, the fuel consumption will also increase. This happens because the higher the engine speed, the higher the amount of fuel burned in the combustion chamber. (3) Has the effect of fuel consumption on the use of roller weight variations and variations of engine speed. This effect lies in the average fuel consumption using less standard rollers when compared to using lighter or heavier rollers. Overall, if you take the best, then the right choice is a standard 12 grams roller, because it has the lowest average fuel consumption value.